Virtual Surgical Planning of Deep Circumflex Iliac Artery Flap for Midface Reconstruction - Kang, Yi-Fan; Lv, Xiao-Ming; Qiu, Shi-Yu; Ding, Meng-Kun; Xie, Shang; Zhang, Lei; Cai, Zhi-Gang; Shan, Xiao-Feng (Frontiers in Oncology, 2021)
Objective: Midface reconstruction is challenging for functional and esthetic reasons. The present study analyzed the effect of virtual surgical planning (VSP) of the deep circumflex iliac artery (DCIA) flap for midface reconstruction. Patients and Methods: Thirty-four patients who underwent midface reconstruction with the DCIA flap were included in this retrospective study. Of the 34 patients, 16 underwent preoperative VSP, which used a three-dimensionally printed surgical guide, computer-assisted navigation system, and pre-bent titanium implants to transfer VSP into real-world surgery. The other 18 patients underwent traditional midface reconstruction. The following were compared between the two groups: bony contact rate in the buttress region (BCR), dental arch reconstruction rate (DAR), surgical approach, position of vascular anastomosis, and dental implantation rate. The independent-samples t-test and Fisher’s exact test were used for analysis. P < 0.05 was considered statistically significant. Results: In total, 12 males and 22 females were included in this study. All patients underwent midface reconstruction using the DCIA flap at the same institution. The median age of patients was 33 years (range: 16–68 years). The average BCR and DAR values in the VSP group were 59.4% ± 27.9% and 87.5% ± 18.9%, respectively, which were significantly higher compared with the non-VSP group (P = 0.049 and P = 0.004, respectively). The dental implantation rate in the VSP group (50.0%) was significantly higher compared with the non-VSP group (11.1%; P = 0.023). The intraoral approach for tumor ablation and vascular anastomosis was the most frequent choice in both groups. There was no significant difference between the two groups. All patients were satisfied with facial symmetry postoperatively. Conclusions: VSP could effectively augment the effect of midface reconstruction with the DCIA flap. Stronger bone contact in the buttress region and higher DAR provide more opportunity for dental implantation, which might be the best solution to improve masticatory function in patients with midface defects.